The Moscow sleeper - Rimington, Stella (Liz Carlyle series, 2018)
A Russian immigrant lies dying in a hospice in upstate Vermont. When a stranger visits, claiming to be a childhood friend, the FBI is alerted and news quickly travels to MI5 in London. Liz Carlyle and her colleague Peggy Kinsolving are already knee-deep in conspiracies, and as they unravel the events that landed the man in the hospital, Liz learns of a network of Russians and their plot to undermine the German government. Liz and Peggy set out to locate and stop this insidious network, traveling the world from Montreal to Moscow.